If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2r + -6r = 8 + -7r Combine like terms: -2r + -6r = -8r -8r = 8 + -7r Solving -8r = 8 + -7r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '7r' to each side of the equation. -8r + 7r = 8 + -7r + 7r Combine like terms: -8r + 7r = -1r -1r = 8 + -7r + 7r Combine like terms: -7r + 7r = 0 -1r = 8 + 0 -1r = 8 Divide each side by '-1'. r = -8 Simplifying r = -8
| 2-15y=5(-3y+2) | | 75C^2-192=0 | | 4x-2=-8+6x+x | | 3p+14=-24+5p | | 5.1q-3.5-4.69=0.5-2.4 | | 4(2-2X)-5(6-X)= | | 2x+-7=0.1(-7+3) | | -x^2+2x+.25=3 | | 3+7(x+8)=87 | | -x^2-2x+.25=3 | | .5x+x+1.25x= | | 11x=20x+8 | | 5(w+1)=3(w+1) | | 5(y+5)=21 | | 18.5+2.25h=47.75 | | 8(4v+4)=4(5+7V) | | 7-8b=10-b | | -3a+5a=-(4a+4)-(-a+1) | | -5h+3=-7 | | 5(y+7)=21 | | 4.65-4.79=13.57-6.84x | | -3a+5a=-(4a+4)-(-1+1) | | 92=86+a/2 | | 15=12+logx | | -4(8-x)+3=2+4(x+4) | | 4(-10)(-1)+9(-10)= | | t+86/2=92 | | (u-1)(u-3)=48 | | 8x+5x+4+8=8x+4+4x | | 12+5y=2y-9 | | 2-3a/4=5 | | a^2=-9a |